The Persian Language Version of the Obsession With the COVID-19 Scale for Adolescents - Asanjarani, Faramarz; Szczygieł, Monika; Arif, Amna (Frontiers in Psychiatry, 2021)
The worldwide pandemic of coronavirus disease (COVID-19) has caused significant public health burdens and psychological dysfunctions. In this challenging time, adolescents require special care. The Persian version of the Obsession with COVID-19 Scale (OCS) for adolescents was developed to screen for dysfunctional obsession associated with the coronavirus during the global pandemic. The structure and internal consistency of the OCS were established. Although there are different language versions of the OCS, this is the first study to validate the psychometric properties of the OCS in Iranian adolescents. Seven hundred and nine students (369 girls) participated in the study. Demographic questions and the OCS were administered. The findings provided support for the existence of a unidimensional structure that met the criteria for configural, metric, and full scalar invariance across gender (girls and boys), inhabitancy (urban and rural), and infection experience (infected and non-infected). The OCS is short and highly reliable measurement. However, further research is necessary to establish the validity of the scale in Iranian population. The development of such valid scales tools is an essential part of both research and practice during times of crisis, like a global pandemic. Diagnosis of pandemic related obsessive thoughts in adolescents is needed as the COVID-19 pandemic is still ongoing and as experts point out, it can be expected that the effects of the pandemic will be observed in the coming years. The Persian version makes it possible to conduct international comparative research on the anxiety related to the COVID-19 pandemic.